2021
DOI: 10.1055/a-1339-0724
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study of virtual reality as an alternative to pharmacological sedation during colonoscopy

Abstract: Background and study aims Conscious sedation is routinely administered for colonoscopy but is associated with risks and inconveniences. We sought to determine whether virtual reality (VR) may be a feasible alternative. Patients and methods Twenty-seven individuals scheduled for screening/surveillance colonoscopy participated. The VR device was activated throughout the colonoscopy, but subjects could opt out and request standard medications. Questionnaires were administered, and variables were assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The results showed that the one participant that requested medication had the lowest score of 1 (weakest motivation) to the question regarding the cause for using iVR as an alternative to sedation, compared with the other 26 participants that completed iVR colonoscopy without requesting medication averaging scores in the range of 8.5–9 out of 10. Therefore, they suggest that a strong motivation for choosing iVR might be related to the patient’s determination to avoid sedation medication [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the one participant that requested medication had the lowest score of 1 (weakest motivation) to the question regarding the cause for using iVR as an alternative to sedation, compared with the other 26 participants that completed iVR colonoscopy without requesting medication averaging scores in the range of 8.5–9 out of 10. Therefore, they suggest that a strong motivation for choosing iVR might be related to the patient’s determination to avoid sedation medication [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The protocol of Çakır and Evirgen, 2021, was submitted to evaluate a Non-Interventional Clinical Research Ethics Committee [ 31 ]. Friedman et al, 2021 [ 32 ] eluded an Ethical Committee approval, motivated by the exclusion of participants with contraindications to conscious sedation, to ensure the possibility of eventual pharmacological rescue. As an emerging technology, iVR may be perceived as non-interventional.…”
Section: Discussionmentioning
confidence: 99%
“…VR has been used to treat anxiety, depression, and pain (6)(7)(8)(9)(10)(11). In gastroenterology, VR lowers endoscopic analgesia requirements and reduces pain from dyspepsia and sphincter of Oddi dysfunction (12)(13)(14)(15)(16)(17)(18)(19)(20). Although use of VR for IBS has been proposed (21), there are no IBS-specific programs nor any programs devoted to gut-directed CBT.…”
Section: Introductionmentioning
confidence: 99%